China releases world's first Tibetan-language office software. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2008)
The article reports that China has released the Neo-shine Tibet Office 3.0, which is the world's first Tibetan-language office software. The software was developed by China Standard Software Co. Ltd. and Tibet University to promote the development of Tibet's information industry. Moreover, the software is the world-leading business because the programmers have tackled the coding and input of the Tibetan language.